The Roles of Head Teachers in the Implementation of Multiple School Accountability in Managing Public Primary Schools in Handeni District, Tanzania. - Vuje, Salimu; Juhudi, Cosmas; Pambas, Tandika (Papanda Publisher, 2025)
The quality of school management to head teachers in public primary schools has become a central issue for the government of Tanzania. Head teachers are considered persons in authority who manage the public primary school and the pillars of educational management. Without effective roles of head teachers in implementing multiple school accountability in managing public primary schools, the provision of quality education and quality of education management cannot be realized in public primary schools in Tanzania. In this context, this paper explores the roles of head teachers in implementing multiple school accountability in managing public primary schools in Handeni district, Tanzania. The study employed a qualitative research approach with interviews and Focus Group Discussions (FGDs) as the primary data collection method. Data needed for this case study design was collected from 42 participants and analyzed by using thematic analysis with the help of SPSS program version 25. Study findings indicate that head teachers implement multiple school accountability in managing public primary schools through planning, communicating, mobilizing, decision-making, and collaborating. Based on the findings, the study recommends that head teachers can more effectively cooperate with various education stakeholders in managing public schools and innovation practices to enhance the teamwork between schools and the community to strengthen school management partnerships.